RADICAL SCAVENGING ACTIVITY OF SELECTED MEDICINAL PLANTS FROM LIMPOPO PROVINCE OF SOUTH AFRICA - Chauke, Alina Mildred; Shai, L J; Mogale, Alfred Molatelo; Mogale, Alfred Molatelo (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Plants collected from Limpopo province of South Africa were investigated for their antioxidative potential using the DPPH radical scavenging assay. Acetone extracts of Flueggea virosa had the highest antioxidant activity with an IC50 value of 30 μg/ml, closely matching the ascorbic acid with an IC50 value of 25 μg/ml. The lowest antioxidant readings were observed with extracts of Rhynchosia venulosa (root extract) and Ficus ingens (leaf extract). Acetone extract of Bridelia virosa leaves had the highest phenolic content (156 mg GAE/g extract), while the lowest content was recorded for R. venulosa root extract and leaf extract of F. ingens (8.3 and 17.7 mg GAE/g extract, respectively). There was a linear correlation between antioxidant activity and total phenolic content. Extracts with high phenolic content had low IC50 values, while extracts with low phenolic concentrations had high IC50 values.